Разработка прогманого обеспечения систем управления авионики - Галкин, П. В. (ХНУРЕ, 2020)
This paper provides an analysis of embedded avionics control systems. New technical solutions for building fault-tolerant computing systems include the “full connected network” and “double star” topologies. Flying sensor networks can be used as auxiliary systems for aviation.
Keywords: система управления авионики; RTCA\DO-178B